A review of developments in carbon dioxide storage - Aminu, Mohammed Dahiru; Nabavi, Seyed Ali; Rochelle, Christopher A.; Manovic, Vasilije (Elsevier, 2017)
Carbon capture and storage (CCS) has been identified as an urgent, strategic and essential approach to reduce anthropogenic CO2 emissions, and mitigate the severe consequences of climate change. CO2 storage is the last step in the CCS chain and can be implemented mainly through oceanic and underground geological sequestration, and mineral carbonation. This review paper aims to provide state-of-the-art developments in CO2 storage. The review initially discussed the potential options for CO2 storage by highlighting the present status, current challenges and uncertainties associated with further deployment of established approaches (such as storage in saline aquifers and depleted oil and gas reservoirs) and feasibility demonstration of relatively newer storage concepts (such as hydrate storage and CO2-based enhanced geothermal systems). The second part of the review outlined the critical criteria that are necessary for storage site selection, including geological, geothermal, geohazards, hydrodynamic, basin maturity, and economic, societal and environmental factors. In the third section, the focus was on identification of CO2 behaviour within the reservoir during and after injection, namely injection-induced seismicity, potential leakage pathways, and long-term containment complexities associated with CO2-brine-rock interaction. In addition, a detailed review on storage capacity estimation methods based on different geological media and trapping mechanisms was provided. Finally, an overview of major CO2 storage projects, including their overall outcomes, were outlined. This review indicates that although CO2 storage is a technically proven strategy, the discussed challenges need to be addressed in order to accelerate the deployment of the technology. In addition, beside the necessity of techno-economic aspects, public acceptance of CO2 storage plays a central role in technology deployment, and the current ethical mechanisms need to be further improved.
Keywords: Carbon capture and storage; Geologic CO2 storage; CO2 storage reservoir; CO2 storage projects